Epitaxial growth of orthorhombic NaTaO3 crystals on SrTiO3 (100) surface by flux coating. Issue 47 (5th November 2015) - Suzuki, Sayaka; Wagata, Hajime; Yubuta, Kunio; Oishi, Shuji; Teshima, Katsuya
Abstract : Flux growth of (10−1)-oriented epitaxial orthorhombic NaTaO3 crystals on SrTiO3 (100) substrate was achieved. Abstract : Orthorhombic NaTaO3 crystals were epitaxially grown on a SrTiO3 (100) surface using flux coating. The selected-area electron diffraction results revealed that the well-oriented orthorhombic NaTaO3 crystals and SrTiO3 had an orientation relationship of (10−1)[010] NaTaO3 //(100)[010] SrTiO3 .